Low occurrence and clonal relatedness of multi-drug resistant Escherichia coli carrying transmissible colistin resistance mcr-1 genes in Ugandan poultry - Wainaina, M.; Ndoboli, Dickson; Ayebare, Dreck; Mbatidde, Irene; Roesel, Kristina; Hammerl, J.A.; Moodley, Arshnee; Tenhagen, B.-A.; Binsker, U. (Frontiers Media, 2025)
Introduction: Colistin resistance is an emerging global health concern that can lead to limited treatment options for life-threatening human infections. Colistin has widespread use in agriculture in many countries to boost livestock health and productivity. Mobile colistin resistance (mcr) genes have been reported globally and facilitate the spread of colistin resistance, but there is limited data on their occurrence in Uganda. This study aimed to identify and characterise mcr-carrying Escherichia coli from semi-intensive and free-ranging poultry farms in Uganda.